2020
DOI: 10.2514/1.j059273
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Analysis of Counter-Rotating Open Rotors with a Locked Blade Row

Abstract: Counter Rotating Open Rotors (CROR) have the potential to reduce environmental emissions thanks to their high propulsive efficiency. However, there are a number of concerns surrounding their acoustic emissions. This contribution presents a novel multi-configuration CROR that offers considerable noise reductions. In particular, we consider locking either fore or aft rotor during takeoff , with the running rotor providing the required thrust. During cruise, both rotors are operated to retain the high efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…However, earlier work involving the Fairey Gannet [6,7] demonstrated the importance of the potential field interactions, particularly for the unsteady loading on the fore r otor. Furthermore, recent work by the present authors [8] also showed the importance of the upstream interactions. These results showed that with AIAA low-solidity blade designs the upstream interactions were as important as the downstream interactions.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, earlier work involving the Fairey Gannet [6,7] demonstrated the importance of the potential field interactions, particularly for the unsteady loading on the fore r otor. Furthermore, recent work by the present authors [8] also showed the importance of the upstream interactions. These results showed that with AIAA low-solidity blade designs the upstream interactions were as important as the downstream interactions.…”
Section: Introductionsupporting
confidence: 71%
“…The HMB3 solver has been validated for a range of rotor flow cases [47][48][49]. Furthermore, the authors have previously shown the ability of the HMB3 solver in predicting open rotor flows [8,50].…”
Section: A the Hmb Solver And Cfd Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a method to reduce noise emissions during takeoff is by locking the aft blade row (working as a stator) (Smith et al, 2020). This will decreases the noise generated by the aft rotor, in all directivities.…”
Section: Contrarotating Open Rotorsmentioning
confidence: 99%
“…Refs. [33][34][35][36]. It has also been used in previous simulation and optimisation studies of ducted rotors [13,17].…”
Section: A Numerical Validationmentioning
confidence: 99%